POPULARIZATION OF THE ART OF BAKHSHI AMONG YOUTH: PROBLEMS AND SOLUTIONS - Naurizbaeva Xanzada Oralbay Qizi (World Scientific Research Journal, 2025)
This article analyzes the issue of the art of bakhshi and its popularity among young people. Bakhshich is one of the ancient and rich types of folk oral art, and today its preservation and wide promotion among the younger generation is one of the urgent problems. The article highlights the cultural and spiritual significance of bakhshich, the interest of young people in this art, existing problems - lack of attention in the education system, the influence of modern media and lack of motivation. Also, effective solutions to these problems are proposed - including bakhshich in educational programs, organizing competitions and festivals for young artists, and promoting it on digital platforms.